Pattern of Utilization of Cervical Cancer Screening Services among Female Sex Workers in Some Selected Brothels in Abuja, Nigeria - Rose Ekama Ilesanmi; Dayo Ruth Kehinde (Elsevier, 2018)
Objective: The utilization of cervical cancer screening services remains low among Female Sex Workers (FSWs) in Sub-Saharan Africa, with few or no studies conducted in Nigeria. However, the prevalence of human papillomavirus in this population is reportedly high because of associated risk factors. This study examined the pattern of cervical cancer screening service utilizations among FSWs in the Abuja metropolis. Methods: This descriptive cross-sectional survey used a purposive sampling technique to select 406 respondents via a structured questionnaire including questions regarding whether they had been screened for cervical cancer, the frequency of screening and type of screening method. Data were analyzed using SPSS version 22 and presented using frequency tables and percentages. Results: The response rate among the participants was 97.6%. The mean age of the FSWs was 32 ± 5.1 years. Regarding the pattern of screening age, the mean age at the first screening was 28 ± 4.3 years. Only 81 (20%) participants had been screened annually, and visual inspection with acetic acid was most frequently used (20.9%). Respondents preferred to undergo screening in their brothels. The awareness of screening services was high (n = 290, 71.4%); however, the utilization of cervical cancer screening services remained low, as 246 (60.6%) FSWs had never been screened. The nonutilization of screening services was related to poor accessibility and a lack of awareness and interest. Conclusions: Although a high level of awareness that would be expected to influence uptake, cervical cancer screening services were rather underutilized by the study respondents. Therefore, a concerted effort is needed to ensure that FSWs understand cervical cancer and its consequences. Hopefully, this effort will improve the uptake.